Integration of Traditional Indonesian Water Games in Freestyle Swimming Training: Effects on Performance, Stroke Mechanics, and Training Engagement Among Youth Athletes - Rezki, Rezki; Yulianti, Mimi; Zahratul habibah, Zahratul habibah; Li, Zhen; Kabir, Md Shahariar (INSPIREE: Indonesian Sport Innovation Review, 2025)
The  purpose  of  the study. This study investigated the efficacy of a novel freestyle swimming training model that systematically integrates traditional Indonesian water games on 50-meter freestyle swimming performance, stroke mechanics, and training enjoyment among youth competitive swimmers. Materials and methods. Twenty-four athletes (14 males, 10 females; age 12-16 years; mean experience 3.4 ± 1.1 years) from the Bangkinang City Swimming Association, Riau, Indonesia participated in this study. A rigorous one-group pretest-posttest experimental design was implemented over an eight-week intervention period (March-May 2023). The training program strategically incorporated five traditional Indonesian water games (Benteng Air, Apung Berlomba, Berenang Bebek, Selam Harta Karun, and Kejar Tangkap Air), each modified to emphasize specific freestyle swimming elements. Comprehensive assessments included 50-meter freestyle time trials, stroke rate, distance per stroke, technical execution ratings, and training enjoyment measures. Results. Statistical analysis demonstrated highly significant improvements in all performance parameters following the intervention. The mean 50-meter freestyle time decreased from 32.46 ± 3.21 seconds pre-intervention to 30.18 ± 2.87 seconds post-intervention (p < 0.001, d = 1.86), representing a 7.02% improvement. Stroke mechanics showed concurrent enhancement, with stroke rate improving by 8.17% (p < 0.001) and distance per stroke increasing by 5.34% (p = 0.003). Technical execution scores improved by 16.57% (p < 0.001). Multiple regression analysis identified three key predictors explaining 78.6% of performance improvement variance: enhanced stroke efficiency (β = 0.47, p < 0.001), training enjoyment (β = 0.31, p = 0.008), and initial technical proficiency (β = -0.25, p = 0.022). Importantly, physiological monitoring confirmed that traditional game activities elicited training stimuli comparable to conventional interval training (mean HR: 162 ± 14 bpm vs. 168 ± 12 bpm, p = 0.075). Conclusions. The integration of culturally relevant traditional games into freestyle swimming training provides a scientifically validated and particularly effective methodology for enhancing swimming performance among youth athletes. This innovative approach simultaneously improves stroke mechanics, physiological conditioning, and technical proficiency while significantly increasing training enjoyment and engagement. The concurrent improvement in typically opposing parameters (stroke rate and distance per stroke) suggests that traditional movement patterns may naturally facilitate the development of efficient propulsive mechanisms. These findings have significant implications for swimming pedagogy, particularly in culturally diverse contexts, offering coaches an evidence-based alternative to conventional training approaches that may enhance both performance outcomes and program adherence.